Morphological and molecular characterization of Thelohanellus macrovacuolaris n. sp. (Myxosporea: Bivalvulida) infecting the palate in the mouth of common carp Cyprinus carpio L. in China. Issue 4 (August 2016) - Liu, Yang; Zhai, Yanhua; Gu, Zemao
Abstract: Thelohanellus macrovacuolaris n. sp. is described during a survey on myxozoan diversity of common carp Cyprinus carpio L. in China. It is characterized by the presence of round or ellipsoidal plasmodium in the palate in the mouth of host. Mature spores were pyriform in frontal view, lemon shaped in lateral view, measuring 21.6 ± 0.9 (19.3–23.8) long, 12.5 ± 0.7 (10.3–13.6) wide, and 10.2 ± 0.4 (9.8–11.8) thick. Most spores were surrounded by the membrane sheath. Single polar capsule was round with an apophysis at its top end presented close to apex of spore, measuring 9.1 ± 0.6 (8.0–10.0) in length, 8.6 ± 0.5 (7.8–9.6) in width. Polar filaments coiled, with 7 to 8 turns. A large, round iodinophilous vacuole was present, with 5.8–7.5 in diameter. The present species is morphologically distinct from all other Thelohanellus species. The BLAST search indicated that the newly obtained small subunit ribosomal RNA (ssrRNA) gene sequence of T. macrovacuolaris n. sp. did not match any available sequences in GenBank. Phylogenetically, T. macrovacuolaris n. sp. was placed sister to Thelohanellus wangi in the Thelohanellus clade. Both morphology and ssrRNA gene sequence data revealed that the present parasite is a new species of genus Thelohanellus . Graphical abstract: Thelohanellus macrovacuolaris n. sp. from the palate of common carp. Highlights: Spore morphology of T. macrovacuolaris n. sp. was distinct from described species. The ssrRNA gene sequences of T. macrovacuolaris n. sp. did not match any sequences. T. macrovacuolaris n. sp. was placed in the Thelohanellus clade.